Mrs. Grant and Madame Jule : a novel - Chiaverini, Jennifer (New York, N.Y. : Dutton, 2015)
"Imagines the inner life of Julia Grant, beloved as a Civil War general's wife and the First Lady, yet who grappled with a profound and complex relationship with the slave who was her namesake-until she forged a proud identity of her own"--
Keywords: Grant, Julia Dent, -- 1826-1902 -- Fiction; African American women -- Fiction; Female friendship -- Fiction; First ladies -- Fiction; Historical fiction